Uso de implantes zigomáticos na fixação de próteses bucomaxilofaciais - Goiato, Marcelo Coelho [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Pereira, Leonardo Viana; Bannwart, Lisiane Cristina; Medeiros, Rodrigo Antonio de; Miyahara, Glauco Issamu [UNESP]; Santos, Daniela Micheline dos [UNESP] (Instituto Metodista de Ensino Superior, 2014)
The maxillofacial prosthetic rehabilitation aims of individuals with craniofacial deformities resulting from trauma, congenital malformations or tumors. Many researches have been done to improve the stability and retention of dentures in patients. With the advent of osseointegration, the maxillofacial prosthesis suffered a major advance making possible the realization of prosthetic works with stability, aesthetic quality and predictable results. This paper reviews the literature regarding the use of zygomatic implants in the fixation of maxillofacial prostheses.

A prótese bucomaxilofacial tem como objetivo a reabilitação de indivíduos com deformidades craniofaciais, decorrentes de traumatismos, más formações congênitas ou tumores. Muitas pesquisas foram realizadas para melhorar a estabilidade e retenção das próteses em pacientes mutilados. Com o advento da osseointegração, a prótese bucomaxilofacial sofreu um grande avanço tornando possível a realização de trabalhos protéticos com estabilidade, qualidade estética e resultados previsíveis. Esse trabalho faz uma revisão de literatura a respeito do uso de implantes zigomáticos na fixação de próteses bucomaxilofaciais.
Use of zygomatic implants in the fixacion of maxillofacial prothesis
Keywords: Maxillofacial prosthesis; Maxillofacial prosthesis implantation; Quality of life; Prótese maxilofacial; Implante; Qualidade de vida